Interactions between star polymers: High-order calculations of the scaling exponents - Schulte-Frohlinde, V.; Holovatch, Yu.; von Ferber, C.; Blumen, A. (Condensed Matter Physics, 2003)
The scaling behavior of star polymers can be calculated in the m → 0 limit of an m -component spin system with an additional composite operator. The resulting scaling exponents describe the effective interaction of such polymer stars, i.e. objects whose behavior interpolates between that of polymer coils and that of hard sphere colloidal particles. We extend the existing renormalization group calculations from the third to the fourth order. Аналіз масштабної (скейлінгової) поведінки зіркових полімерів можна проводити на основі границі m → 0 m -компонентної спінової системи з додатковим композитним оператором. Скейлінгові показники, які при цьому отримуються, описують ефективну взаємодію полімерних зірок: об’єктів, поведінка яких інтерполює між поведінкою полімерних клубків та колоїдних частинок. Ми доповнюємо існуючі ренормгрупові обчислення третього порядку теорії збурень четвертим.